1994
DOI: 10.1007/bf00140484
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and excretion of lanthanides: comparison between europium salts and complexes

Abstract: Europium (152,154Eu) was intravenously injected into rats as: (i) the chloride salt at pH 7.4, (ii) the chloride salt at pH 3, (iii) the albumin complex and (iv) the DTPA complex, and tissue uptake was determined 24 h later. For the chlorides, the target organ for uptake was liver (about 60% of dose) whilst europium complexes were rapidly excreted in urine and were predominantly taken up into the kidney (about 0.5% of dose) and bone. Liver uptake of EuCl3, pH 7.4, corresponded to that of a colloidal material w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…This, coupled with an acute experiment involving bile duct ligation, by which we achieved experimental obstruction of the extrahepatic biliary system, allowed us to determine with a high degree of confidence that PLGA NPs and their degradation products accumulate in the lower GIT via the liver. Since europium complexes are eliminated through glomerular filtration in kidneys 33 , the europium fluorescence signal in the GIT is highly suggestive that at least a part of the PLGA polymer (or a portion of its non-degraded particles) is still attached to the europium label following hepatobiliary excretion. Even though there is currently a wide nano-scale range available, the nanoparticle size (100 nm) chosen in this study is commonly used in drug delivery research; most importantly, many investigators report off-target nanoparticle clearance by liver (> 80% of the injected dose in many cases), which is likely driven by the size of liver sinusoidal endothelial fenestrations, ranging from 100 to 150 nm 34 .…”
Section: Discussionmentioning
confidence: 99%
“…This, coupled with an acute experiment involving bile duct ligation, by which we achieved experimental obstruction of the extrahepatic biliary system, allowed us to determine with a high degree of confidence that PLGA NPs and their degradation products accumulate in the lower GIT via the liver. Since europium complexes are eliminated through glomerular filtration in kidneys 33 , the europium fluorescence signal in the GIT is highly suggestive that at least a part of the PLGA polymer (or a portion of its non-degraded particles) is still attached to the europium label following hepatobiliary excretion. Even though there is currently a wide nano-scale range available, the nanoparticle size (100 nm) chosen in this study is commonly used in drug delivery research; most importantly, many investigators report off-target nanoparticle clearance by liver (> 80% of the injected dose in many cases), which is likely driven by the size of liver sinusoidal endothelial fenestrations, ranging from 100 to 150 nm 34 .…”
Section: Discussionmentioning
confidence: 99%
“…The salt was taken up by the liver, while the albumin complex was excreted rapidly into the urine, suggestive of a weak interaction between Eu 3+ and albumin in serum. 87 Intriguingly, La 2 (CO 3 ) 2 is a potential noncalcium phosphate binding drug. Its surprisingly low systemic toxicity is ascribed to its low solubility in physiological fluids.…”
Section: Methods Of Lanthanide Deliverymentioning
confidence: 99%
“…Work sponsored by Johnson Matthey at the University of Surrey, UK, highlighted the ease with which the lanthanides formed precipitates with phosphate, frequently a challenge for the investigator. 29,30 In collaboration with Shire Pharmaceuticals a project was initiated to examine lanthanides as phosphate binders for hyperphosphatemia. In vitro phosphate binding studies comparing a number of lanthanide salts and complexes identified lanthanum carbonate as having good phosphate binding properties.…”
Section: Lanthanum Carbonate For the Management Of Hyperphosphatemiamentioning
confidence: 99%